The female nude: art, obscenity, and sexuality - Nead, Lynda (Routledge, 1992)
The history of Western art is saturated with images of the female body. Lynda Nead's The Female Nude was the first book to critically examine this phenomenon from a feminist perspective and ask: how and why did the female nude acquire this status? In a deft and engaging manner, Lynda Nead explores the ways in which acceptable and unacceptable images of the female body are produced, issues which have been reignited by current controversies around the patriarchy, objectification and pornography. Nead brilliantly illustrates the two opposing poles occupied by the female nude in the history of art; at one extreme the visual culmination of enlightenment aesthetics; at the other, spilling over into the degraded and the obscene. What both have in common, however, is the aim of containing the female body. Drawing on examples of art and artists from the classical period to the 1980s, The Female Nude paints a devastating picture of the depiction of the female body and remains as fresh and invigorating today as it was at the time of its first publication.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; 1970-1979; 1980-1989; antiquité; approches et analyses; arts; corps; cours; discipline; féminisme pop; har4600; histoire de l'art; moyen-âge; nudité; premier cycle; périodes historiques; représentation des femme*; sexisme; systèmes d'oppressions; thématiques

La question de l'identité dans l'écriture de Pauline Julien - Rheault, Michel (Université du Québec à Montréal, 1991)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; amériques; arts; discipline; femmes* artistes; mémoires/thèses; périodes historiques; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires